2018
DOI: 10.1029/2018sw001814
|View full text |Cite
|
Sign up to set email alerts
|

Transformer‐Level Modeling of Geomagnetically Induced Currents in New Zealand's South Island

Abstract: During space weather events, geomagnetically induced currents (GICs) can be induced in high‐voltage transmission networks, damaging individual transformers within substations. A common approach to modeling a transmission network has been to assume that every substation can be represented by a single resistance to Earth. We have extended that model by building a transformer‐level network representation of New Zealand's South Island transmission network. We represent every transformer winding at each earthed sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
111
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(119 citation statements)
references
References 26 publications
6
111
0
2
Order By: Relevance
“…However, there is evidence that GMD may produce significant GIC further equatorwards, where no DC monitors are located. For example the GIC modeling reported by Divett et al (2018) showed that significant GIC is expected to occur at the top of the South Island.…”
Section: Experimental Data Setsmentioning
confidence: 99%
“…However, there is evidence that GMD may produce significant GIC further equatorwards, where no DC monitors are located. For example the GIC modeling reported by Divett et al (2018) showed that significant GIC is expected to occur at the top of the South Island.…”
Section: Experimental Data Setsmentioning
confidence: 99%
“…This force arises from variations in the magnetic field cutting a loop consisting of the line itself, the grounding points of the line, and a depth in the earth related to the skin depth for the magnetic field variation. Modeling of the induced electric fields and their impact on a specific transmission line topology allows prediction of the severity of the risk presented by GIC to electrical substations, or even individual transformers, in the network (see, for example, Divett et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Striking features of the calculated GIC distribution (Divett et al 2017 their Figure 8) included the high spatial variability in the GIC magnitude, and the small number of affected substations, quite in a similar manner to those observed in the UK (Beggan et al 2013 their Figure 8). A related analysis by Divett et al (2018) expanded this effort to consider transformer-level (rather than substation-level) GICs, thus eliminating one more uncertainty in the interpretation of real, transformer-level GIC measurements.…”
Section: New Zealandmentioning
confidence: 99%